PRAKTIK MENGAJAR EKONOMI PADA PROGRAM SEA TEACHER DI FILIPINA: TINJAUAN SWOT UNTUK PENGUATAN KOMPETENSI PENDIDIK ABAD 21 - Dicky Afrian; Aprizal; Romi Kurniadi (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study explores the experiences of Indonesian pre-service teachers in teaching economics through the SEA Teacher Program Batch IX in the Philippines, using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to strengthen 21st-century educator competencies. The research employs a qualitative phenomenological approach, collecting data through in-depth interviews with four informants who participated in the program. Data analysis was conducted using NVivo 12 software to code and categorize data based on the SWOT framework. The findings reveal that cross-border teaching practice provides professionally and personally enriching experiences. Strengths include material preparation, learning strategy flexibility, and institutional support, while weaknesses emerge from English language limitations and lack of international experience. Opportunities include professional career development, international networking expansion, and exposure to inclusive and professional learning environments. Threats encompass educational system differences, limited program duration, insufficient supporting facilities, and cultural adaptation challenges. The study concludes that the SEA Teacher program significantly impacts the readiness of 21st-century educator candidates, though improvements are needed in program duration, pre-departure training enhancement, and English language proficiency optimization.